Strengthening vaccination frameworks: Findings of a study on the legal foundations of National Immunization Technical Advisory Groups (NITAGs). Issue 4 (22nd January 2020) - Harmon, Shawn H.E.; Faour, David; MacDonald, Noni E.; Graham, Janice; Steffen, Christoph; Henaff, Louise; Shendale, Stephanie
Abstract: In 2017, the Strategic Advisory Group of Experts on Immunization's Assessment Report of the Global Vaccine Action Plan noted the need to " better document the ways in which legislation and regulations have been used to promote or undermine immunization at the national level ". Despite National Immunization Technical Advisory Groups (NITAGs) now existing in over 134 countries worldwide, there has been very little academic consideration of their legal underpinnings. In this paper, we compare the legal foundations and authority of 28 NITAGs from the six WHO Regions. All are members of the Global NITAG Network. We categorize the NITAGs based on their legal foundation and on the authority granted to them by their government, organizing them into a taxonomy of models. We then propose legal considerations for governments contemplating establishing or reforming a NITAG.